Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults. - Wasiuk, Peter A.; Cook, Barbara A.; Irwin, Julia R. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Autistic adults consistently report difficulties understanding speech in adverse listening environments, which may be related to differences in social communication and participation. Research examining masked-speech recognition in autistic adults is limited, particularly in competing speech backgrounds with high degrees of informational masking. This work characterizes speech-in-speech and speech-in-noise recognition in young adults on the autism spectrum, as well as evaluates self-reported functional listening abilities and listening-related fatigue. Method: Masked-speech recognition was evaluated in both autistic (n = 20) and non-autistic (n = 20) young adults with normal hearing. Speech reception thresholds were adaptively measured in two-talker speech and speech-shaped noise using target sentences that were either semantically meaningful or anomalous. Functional listening abilities and listening-related fatigue were assessed using the Speech, Spatial, and Qualities of Hearing Scale and the Vanderbilt Fatigue Scale for Adults. Autism characteristics and social communication experiences were quantified using the Social Responsiveness Scale-Second Edition. Results: Autistic adults displayed significantly poorer speech-in-speech recognition than their non-autistic peers, while speech-in-noise recognition did not differ between groups. Functional listening difficulties in daily life and listeningrelated fatigue were significantly higher for autistic participants. Autism characteristics strongly predicted functional listening abilities and listening-related fatigue in both groups. Conclusions: Autistic young adults experience objective speech-in-speech recognition difficulties that correspond with listening challenges in daily life. Autism characteristics and social communication experiences predict functional listening abilities reported by both autistic and non-autistic young adults with normal hearing. Speech-in-speech recognition difficulties observed here may amplify social communication challenges for adults on the autism spectrum. Future work must prioritize improved awareness of autistic listening differences.